BreathDx – molecular analysis of exhaled breath as a diagnostic test for ventilator–associated pneumonia: protocol for a European multicentre observational study. Issue 1 (December 2017) - van Oort, Pouline; Nijsen, Tamara; Weda, Hans; Knobel, Hugo; Dark, Paul; Felton, Timothy; Rattray, Nicholas; Lawal, Oluwasola; Ahmed, Waqar; Portsmouth, Craig; Sterk, Peter; Schultz, Marcus; et al.
Abstract Background The diagnosis of ventilator-associated pneumonia (VAP) remains time-consuming and costly, the clinical tools lack specificity and a bedside test to exclude infection in suspected patients is unavailable. Breath contains hundreds to thousands of volatile organic compounds (VOCs) that result from host and microbial metabolism as well as the environment. The present study aims to use breath VOC analysis to develop a model that can discriminate between patients who have positive cultures and who have negative cultures with a high sensitivity. Methods/design The Molecular Analysis of Exhaled Breath as Diagnostic Test for Ventilator-Associated Pneumonia (BreathDx) study is a multicentre observational study. Breath and bronchial lavage samples will be collected from 100 and 53 intubated and ventilated patients suspected of VAP. Breath will be analysed using Thermal Desorption – Gas Chromatography – Mass Spectrometry (TD-GC-MS). The primary endpoint is the accuracy of cross-validated prediction for positive respiratory cultures in patients that are suspected of VAP, with a sensitivity of at least 99% (high negative predictive value). Discussion To our knowledge, BreathDx is the first study powered to investigate whether molecular analysis of breath can be used to classify suspected VAP patients with and without positive microbiological cultures with 99% sensitivity. Trial registration UKCRN ID number 19086, registered May 2015; as well as registration atwww.trialregister.nl under the acronym 'BreathDx' with trial ID numberNTR 6114 (retrospectively registered on 28 October 2016).